Strengthening The Religious Character Of Students Through The Mosque Youth Organization At SMKN 1 Probolinggo - Cahayawati, Kartika; Hadi, Muhammad Fazlur Rahman; Jayadi, Mahsun (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to determine the role of the Mosque Youth organization in strengthening the religious character of students at SMKN 1 Probolinggo. Adolescence is an important period in individual development, where they experience biological, psychological and social changes. In this context, the role of the Mosque Youth organization has a significant impact in guiding students to develop religious and moral awareness through routine activities, incidental activities and Ramadan activities. This organization helps students strengthen prayer skills, increase religious understanding, and expand social networks. The results of the interviews showed that students felt happy and were actively involved in the activities of the Mosque Youth organization, which had an impact on increasing religious awareness and the quality of their worship. In conclusion, it is hoped that the success of the Mosque Youth organization in strengthening the religious character of students can be used as an example for other educational institutions in forming a religious and responsible generation.